Mastering statistics - Hannagan, T.J. (Macmillan London, 1986)
The aims of this book are to provide a complete statistical foundation for a wide variety of readers, some of whom may have very limited mathematical knowledge. The book includes a chapter on simple arithmetic as a reminder of basic mathematical techniques
Includes Index
aia 29/09/2017
Loans
Keywords: Mathematical statistics; Statistical mathematics; Statistics